Positron scattering and transport in liquid helium. (9th October 2020) - Cocks, D G; McEachran, R P; Boyle, G J; Cheng, E; White, R D
Abstract: In previous papers we have proposed a method for the ab initio calculation of fully differential cross-sections for electron scattering in liquids and applied it to liquid argon, xenon and krypton. In this paper, we extend the procedure to the consideration of positron scattering in liquid helium, which is complicated by the annihilation process as well as the fact that the electron definition for the region 'owned' by a target atom used previously does not have a positron analogue. We explore several physically motivated definitions to obtain effective positron scattering in the dense fluid. We find that our calculations of a pure helium system cannot precisely match experimental measurements, however by including a small admixture (<0.1%) of an impurity, we can obtain reasonable agreement in the dense gas phase. In contrast, the comparison between our calculations and liquid phase measurements is less satisfactory. This provides motivation to explore further multiple scattering effects in the theory.